2017
DOI: 10.1002/adsc.201700955
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Component Coupling Reactions of Maleimides, Thiols, and Amines: One‐Step Construction of 3,4‐Heteroatom‐functionalized Maleimides by Copper‐Catalyzed C(sp2)−H Thioamination

Abstract: A copper-catalyzed intermolecular thioamination of maleimides with thiols and amines has been developed. A diverse range of 3-amino-4-thiomaleimides and 3,4-dihydropyrrolo [3,4-b][1,4] thiazine-5,7(2H,6H)-diones were obtained with good yields, involving CÀN and CÀS bond formations. This methodology is very practical and features high atom economy, excellent functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 57 publications
0
10
0
2
Order By: Relevance
“…[53,54] In recent times, the intermolecular thioamination of maleimides has been reported with copper catalyst; otherwise, this type of direct coupling of maleimides with amines and thiols are very rare in literature. [55,56] In this work, we have observed that the thioamination of maleimide derivatives occurred with ease under the same standard conditions and notably, acetonitrile was found suitable as a solvent for this transformation (Table 3). At the starting step, N-phenyl substituted maleimide, 1 b successfully underwent this oxidative coupling reaction with substituted benzenethiol (p-CH 3 , p-Cl) and cyclic secondary amines like pyrrolidine, piperidine to afford the final thioaminated products 5 a, 5 b and 5 c respectively with moderate to good yields.…”
Section: Resultsmentioning
confidence: 69%
“…[53,54] In recent times, the intermolecular thioamination of maleimides has been reported with copper catalyst; otherwise, this type of direct coupling of maleimides with amines and thiols are very rare in literature. [55,56] In this work, we have observed that the thioamination of maleimide derivatives occurred with ease under the same standard conditions and notably, acetonitrile was found suitable as a solvent for this transformation (Table 3). At the starting step, N-phenyl substituted maleimide, 1 b successfully underwent this oxidative coupling reaction with substituted benzenethiol (p-CH 3 , p-Cl) and cyclic secondary amines like pyrrolidine, piperidine to afford the final thioaminated products 5 a, 5 b and 5 c respectively with moderate to good yields.…”
Section: Resultsmentioning
confidence: 69%
“…Crystals 2020, 10, x FOR PEER REVIEW 6 of 50 Compound 30 forms C(8) chains by interaction of the imide NH with the remote ester carbonyl oxygen and these are cross-linked by the ring NH to nitro group C (10) interaction resulting in a two-dimensional network containing R 4 4 (31) units (Figure 11) [35]. Compound 31 forms dimers of pattern A by imide NH to CO interaction and these are then further linked in a zig-zag arrangement by dimer formation between the other imide CO and the six-membered ring NH (Figure 12) [36]. This gives an overall designation of C (10) Compound 31 forms dimers of pattern A by imide NH to CO interaction and these are then further linked in a zig-zag arrangement by dimer formation between the other imide CO and the six-membered ring NH (Figure 12) [36].…”
Section: Ring-fused Maleimidesmentioning
confidence: 99%
“…Compound 31 forms dimers of pattern A by imide NH to CO interaction and these are then further linked in a zig-zag arrangement by dimer formation between the other imide CO and the six-membered ring NH (Figure 12) [36]. This gives an overall designation of C (10) Compound 31 forms dimers of pattern A by imide NH to CO interaction and these are then further linked in a zig-zag arrangement by dimer formation between the other imide CO and the six-membered ring NH (Figure 12) [36]. This gives an overall designation of C(10)[ R 2 2 (8), R 2 2 (10)].…”
Section: Ring-fused Maleimidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur-containing disubstituted maleimides are traditionally accessed by several reaction steps, such as the reaction of nitroketene dithioacetal and phenylacetonitriles, , and hence, much effort has been devoted to the development of simpler and accessible methodologies for the preparation of these heterocycles. In this context, Zhao and co-workers, employing the nonsubstituted maleimide as a substrate, synthesized a 3-indolyl-4-thioarylmaleimide in three steps, including a copper iodide-catalyzed thiolation reaction (Scheme A) . Recently, Wu and co-workers were able to achieve 3-methylthio-4-arylmaleimides using simple reactants through a thiol-free annulation strategy promoted by iodide (Scheme B). , The main disadvantage of this protocol is the generation of iodomethane as a hazardous byproduct.…”
Section: Introductionmentioning
confidence: 99%